IOT PENGENDALIAN KEAMANAN PINTU RUMAH OTOMATIS MENGGUNAKAN E-KTP BERBASIS MIKROKONTROLER ESP32 - Deri Setiawan; Basuki Rahmat; Wahyu SJ Saputra (Pusat Riset dan Inovasi Nasional, 2023)
Internet of Things (IoT) is a concept that connects electronic devices to the internet and enables the exchange of data between these devices. In this context, this study aims to develop an automatic door security control system using an ESP32 microcontroller-based e-KTP. The proposed system uses e-KTP as a substitute for a physical key on the door of the house. e-KTP will be connected to the ESP32 microcontroller which acts as the brain of the system. Personal data from the e-KTP, such as identity numbers, will be stored securely and used for user authentication. The ESP32 microcontroller will communicate with the server using the WiFi protocol to send and receive data. Users will be able to access the door of the house wirelessly via a mobile application connected to the server. This mobile application will provide an intuitive user interface to control door access and view security status. This system is also equipped with various security features. In addition, users can also monitor home security in real-time through a mobile application, even when they are not at home.